Synthesis, molecular modelling, and biological evaluation of novel quinoxaline derivatives for treating type II diabetes - Fatmah Ali S. Alasmary; Dalal A. Abdullah; Vijay H. Masand; Abir Ben Bacha; Abdelsattar Mansour Omar Ebeid; Moustafa E. El-Araby; Ahmed M Alafeefy (Taylor & Francis Group, 2024)
Quinoxalines are benzopyrazine derivatives with significant therapeutic impact in the pharmaceutical industry. They proved to be useful against inflammation, bacterial, fungal, viral infection, diabetes and other applications. Very recently, in January 2024, the FDA approved new quinoxaline containing drug, erdafitinib for treatment of certain carcinomas. Despite the diverse biological activities exhibited by quinoxaline derivatives and the role of secretory phospholipase A2 (sPLA2) in diabetes-related complications, the potential of sPLA2-targeting quinoxaline-based inhibitors to effectively address these complications remains unexplored. Therefore, we designed novel sPLA2- and α-glucosidase-targeting quinoxaline-based heterocyclic inhibitors to regulate elevated post-prandial blood glucose linked to patients with diabetes-related cardiovascular complications. Compounds 5a-d and 6a-d were synthesised by condensing quinoxaline hydrazides with various aryl sulphonyl chlorides. Biological screening revealed compound 6a as a potent sPLA2 inhibitor (IC50 = 0.0475 µM), whereas compound 6c most effectively inhibited α-glucosidase (IC50 = 0.0953 µM), outperforming the positive control acarbose. Moreover, compound 6a was the best inhibitor for both enzymes. Molecular docking revealed pharmacophoric features, highlighting the importance of a sulfonohydrazide moiety in the structural design of these compounds, leading to the development of potent sPLA2 and α-glucosidase inhibitors. Collectively, our findings helped identify promising candidates for developing novel therapeutic agents for treating diabetes mellitus.